EFFECTS OF AQUATIC THERAPY ON SLEEP QUALITY AND QUALITY OF LIFE IN PATIENTS WITH ARTERIAL HYPERTENSION - Iamonti, Vinicius Carlos; Vasconcelos, Kelly da Silva; Sato, Vanessa Luzia Baggio; Machado, Renata Saltiel; da Silva, Hyanna Mayra Messias Lina; de Oliveira, Natália Cristina; Kumpel, Claudia (Journal of Interdisciplinary Lifestyle Studies, 2018)
Contextualization: Hypertension is a disease that essentially affects the balance of vasodilator and vasoconstrictor mechanisms, causing an increase in vessels blood pressure that may compromise tissue irrigation and cause damage to the organs. Cases may develop to a severe clinical presentation and affect sleep quality and quality of life of the patients. Objective: To evaluate whether aquatic therapy has a beneficial effect on sleep quality and quality of life in patients with hypertension. Method: All patients completed Berlin, Epworth, Minichal and Pittsburgh questionnaires, Hospital Anxiety and Depression Scale (HAD), and an open questionnaire. Patients participated in twice weekly sessions of aquatic therapy for 5 months. Results: The average age of the sample was 58 ± 8 years old. There was no significant improvement in sleep quality, evaluated by Pittsburgh questionnaire (p = 0.05), however, enhancements in daytime sleepiness (p = 0.0048) as well as in the number of hours of sleep at every 24 hours (p = 0.04), quality of life (p = 0.002) and level of anxiety (p = 0.012). Conclusion: Aquatic therapy is an effective alternative therapy for improving quality of life, decreasing anxiety, daytime sleepiness and reducing the chance of developing sleep apnea.